2022
DOI: 10.3390/nu14040784
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity of Fenugreek Sprout and Seed Extracts and Their Bioactive Constituents on MCF-7 Breast Cancer Cells

Abstract: Trigonella foenum-graecum L. (fenugreek), a member of the legume family (Fabaceae), is a promising source of bioactive phytochemicals, which explains its traditional use for a variety of metabolic disorders including cancer. The current study aimed to evaluate extracts of fenugreek seeds and sprouts, and some of their constituents, to compare their cytotoxic and antiproliferative activities in MCF-7 breast cancer cells. The extracts were chemically characterised using high-resolution accurate mass liquid chrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…Sebastian et al showed that Fenugreek ethanolic extract reduced cell viability and triggered early apoptotic changes such as phosphatidylserine reversal and reduced mitochondrial membrane potential on the breast cancer cell line MCF-7 (13). In a different study, it was shown that both MeOH extracts from Fenugreek sprouts were more effective than those from seeds (14,15). Kaviarasan et al found that Fenugreek had a cytoprotective effect against ethanol-induced cytotoxicity in human liver cells (16).…”
Section: Discussionmentioning
confidence: 99%
“…Sebastian et al showed that Fenugreek ethanolic extract reduced cell viability and triggered early apoptotic changes such as phosphatidylserine reversal and reduced mitochondrial membrane potential on the breast cancer cell line MCF-7 (13). In a different study, it was shown that both MeOH extracts from Fenugreek sprouts were more effective than those from seeds (14,15). Kaviarasan et al found that Fenugreek had a cytoprotective effect against ethanol-induced cytotoxicity in human liver cells (16).…”
Section: Discussionmentioning
confidence: 99%
“…Four compounds of them were isolated for the first time from Z. floridana leaves. These compounds were tested previously in other studies against breast and colon cell lines in vitro and they showed cytotoxic effects [ 2 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 ], which could account for the cytotoxic effect of the n -butanol fraction of Z. floridana. The potent toxoplasmocidal effect of n -BuOH fraction encouraged us to investigate and predict the possible mechanisms of these compounds to inhibit T. gondii using in silico molecular docking study.…”
Section: Discussionmentioning
confidence: 99%
“…Cytotoxicity assays (CTAs) of herbal medicines are dependent on the concentration, mechanism of cytotoxicity, evaluation methods, cell type, components and exposure over time [36–39] . There are several methods for measuring cell sensitivity to herbal extracts, and cytotoxicity evaluation [40,41] . The use of standard test methods for cytotoxicity assessment could enable determination of concentration that may result in higher and lower toxicity [42–44] .…”
Section: Introductionmentioning
confidence: 99%
“…[36][37][38][39] There are several methods for measuring cell sensitivity to herbal extracts, and cytotoxicity evaluation. [40,41] The use of standard test methods for cytotoxicity assessment could enable determination of concentration that may result in higher and lower toxicity. [42][43][44] In vitro cytotoxicity or cell viability assays provide many advantages and disadvantages, which are summarized in Table 1.…”
Section: Introductionmentioning
confidence: 99%